Pattern of Dyslipidemia among Prediabetics of Karnataka State, South India: A Cross Sectional Study - Rao Sujatha N (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
This study aims to explore the possibility of the existence of dyslipidemia among prediabetics in Karnataka state south India and to identify the risk factor(s) if any, for the onset of diabetes. Hyperglycemia can be determined by the glycated hemoglobin (HbA1c) value which indicates the blood glucose level over the past three months. A cross-sectional study involving 310 individuals in Bangalore, Karnataka State, South India from the period of February 2022 to March 2024 was considered for the study. Within the lipid profile, Total cholesterol (TC), High-Density Lipoprotein (HDL) and the ratio of TC to HDL displayed statistically significant differences between the means of the population of healthy nondiabetics and prediabetics. So, testing of TC, HDL and TC to HDL ratio at regular intervals for prediabetics should be made mandatory, as they fall in the risk category for developing type 2 Diabetes and this regular screening of TC, HDL and TC to HDL ratio will prevent prediabetics from progressing into type2 diabetes later on. It is a well-known fact that the HbA1c level as a predicting factor differs among races and ethnicities as the rate of glycation and RBC life span differs among racial and ethnic groups. Regarding demographic factors, abdominal obesity was found to be statistically significantly associated with prediabetes. Prediabetics should implement a regular exercise regime to prevent themselves from becoming diabetics in their later years.